Antioxidant activity and analgesic assessment of Lansium domesticum stem bark infusion - PRATIWI APRIDAMAYANTI; INARAH FAJRIATY; ETNI HATITA (Nusantara Bioscience, 2018)
Apridamayanti P, Fajriaty I, Etni Hatita E. 2018. Antioxidant activity and analgesic assessment of Lansium domesticum stem bark infusion. Nusantara Bioscience 10: 71-75. Langsat (Lansium domesticum Correa) is empirically used as a medicine for fever and pain. This study intended to determine the effectiveness of stem bark infusion of langsat as an antioxidant and analgesic. Antioxidant activity test was performed by DPPH method (2,2 Diphenyl-1-picrilhydrazil), with infusion at concentration of 1000, 2000, 3000, 4000 and 5000 ppm. Absorbance of the sample was measured using a UV-Vis spectrophotometer. The analgesic test was performed on male Swiss mice by Writhing test using acetic acid 0.6%, CMC-Na induced negative control, Paracetamol 65 mg/kg BW induced positive control, dose I (65 mg/kg BW), dose II (130 mg/kg BW) and dose III (195 mg/kg BW). Data was analyzed using One Way ANOVA in SPSS and the percentage of writhing protection at each dose was calculated. The results of phytochemical metabolites screening of stem bark infusion showed the presence of flavonoids, terpenoids/steroids, tannins, phenols and saponins. Antioxidant activity measured by spectrophotometric measurements showed that the antioxidant activity of stem bark infusion was IC50 2820 ?g/ml. The percentage of writhing protection on dose I, II, and III was 57.52%, 42.48% and 24.51% respectively, showing a significant difference with negative control at minute 5, 10 and 15 (P <0, 05). There were no significant differences between positive control and dose I, at minute 30 to minute 60 (P> 0,05). The effective dose of stem bark infusion was obtained as an analgesic at dose of 65 mg/kg BW from 30 to 60 minutes.